This action might not be possible to undo. Are you sure you want to continue?
Add Maths Formulae List: Form 4 (Update 18/9/08)
Absolute Value Function Inverse Function If
f ( x ), if f ( x ) ≥ 0 f ( x)
− f ( x), if f ( x ) < 0
y = f ( x ) , then f −1 ( y ) = x
Remember: Object = the value of x Image = the value of y or f(x) f(x) map onto itself means f(x) = x
02 Quadratic Equations
General Form Quadratic Formula
ax 2 + bx + c = 0
where a, b, and c are constants and a ≠ 0. *Note that the highest power of an unknown of a quadratic equation is 2. Forming Quadratic Equation From its Roots: If α and β are the roots of a quadratic equation
−b ± b 2 − 4 ac x= 2a
When the equation can not be factorized. Nature of Roots
α +β =−
The Quadratic Equation
x 2 − (α + β ) x + αβ = 0
or x − ( SoR ) x + ( PoR ) = 0 SoR = Sum of Roots PoR = Product of Roots
b 2 − 4 ac b 2 − 4 ac b 2 − 4 ac b 2 − 4 ac
>0 =0 <0 ≥0
⇔ two real and different roots ⇔ two real and equal roots ⇔ no real roots ⇔ the roots are real
*Note that the highest power of an unknown of a quadratic function is 2. x = − p min.NET 03 Quadratic Functions General Form Completing the square: f ( x) = ax 2 + bx + c where a. http://www. value = q min. x = − b 2a b ) 2a b 2a (ii) (iii) Quadratic Inequalities a > 0 and f ( x) > 0 a > 0 and f ( x) < 0 min.com ONE-SCHOOL. x = − p Alternative method: a > 0 ⇒ minimum ⇒ ∪ (smiling face) a < 0 ⇒ maximum ⇒ ∩ (sad face) f ( x) = ax 2 + bx + c (i) the value of x. x = − Nature of Roots a b a a< x<b b ⇔ intersects two different points at x-axis 2 b − 4ac = 0 ⇔ touch one point at x-axis b 2 − 4ac < 0 ⇔ does not meet x-axis b 2 − 4ac > 0 x < a or x > b 04 Simultaneous Equations To find the intersection point ⇒ solves simultaneous equation. and c are constants and a ≠ 0. point = (− p./max.http://rahmahsamuri-rahms.linear equation. Remember: substitute linear equation into non.html 2 .one-school. b./max. value = f (− equation of axis of symmetry./max. q) equation of axis of symmetry.net/notes.blogspot. (i) (ii) (iii) (iv) f ( x) = a ( x + p)2 + q the value of x.
blogspot.html 3 . a0 = 1 a m × a n = a m+n a m ÷ a n = a m−n ( a m ) n = a m× n ( ab) n = a n b n m a −1 = 1 a a b ( ) −1 = b a Fractional Index 1 an = a n m an = a n a n an ( ) = n b b Law of Logarithm Fundamental of Logarithm log a y = x ⇔ a x = y log a a = 1 log a mn = log a m + log a n log a log a a x = x log a 1 = 0 m = log a m − log a n n log a mn = n log a m Changing the Base log a b = log c b log c a log a b = 1 logb a http://www.NET 05 Indices and Logarithm Fundamental if Indices Laws of Indices Zero Index.net/notes.one-school.com ONE-SCHOOL.http://rahmahsamuri-rahms. Negative Index.
m = − ⎜ ⎟ ⎝ x − int ercept ⎠ y2 − y1 x2 − x1 Parallel Lines Perpendicular Lines When 2 lines are parallel. m = Or ⎛ y − int ercept ⎞ Gradient of a line.com ONE-SCHOOL.http://rahmahsamuri-rahms.net/notes. m1 × m2 = −1 m1 = m2 . M = ⎜ ⎛ x1 + x2 y1 + y2 ⎞ . When 2 lines are perpendicular to each other. m1 = gradient of line 1 m2 = gradient of line 2 Midpoint A point dividing a segment of a line Midpoint.blogspot. ⎟ 2 ⎠ ⎝ 2 A point dividing a segment of a line ⎛ nx + mx2 ny1 + my2 ⎞ P =⎜ 1 .html 4 . ⎟ m+n ⎠ ⎝ m+n http://www.NET 06 Coordinate Geometry Distance and Gradient Distance Between Point A and C = (x1 − x2 )2 + (x1 − x2 )2 Gradient of line AC.one-school.
y1) and (x2.com ONE-SCHOOL. y2) given given y − y1 y2 − y1 y − y1 = m( x − x1 ) = x − x1 x2 − x1 x-intercept and y-intercept given x y + =1 a b Equation of perpendicular bisector ⇒ gets midpoint and gradient of perpendicular line.http://rahmahsamuri-rahms. Information in a rhombus: A B (i) (ii) (iii) (iv) same length ⇒ AB = BC = CD = AD parallel lines ⇒ mAB = mCD or mAD = mBC diagonals (perpendicular) ⇒ mAC × mBD = −1 share same midpoint ⇒ midpoint AC = midpoint BD any point ⇒ solve the simultaneous equations D C (v) http://www.NET Area of triangle: Area of Triangle = 1 2 1 ( x1 y2 + x2 y3 + x3 y1 ) − ( x2 y1 + x3 y2 + x1 y3 ) 2 A= Form of Equation of Straight Line General form ax + by + c = 0 Gradient form y = mx + c Intercept form m = gradient c = y-intercept x y + =1 a b a = x-intercept b = y-intercept m=− b a Equation of Straight Line Gradient (m) and 1 point (x1. y1) 2 points.html 5 .one-school.net/notes.blogspot. (x1.
y ) which is always at a constant distance from two fixed points A ( x1 .List of Chemical Reactions SPM Form 5 Chemistry .net/notes.http://rahmahsamuri-rahms.blogspot. y ) which is always equidistant from two fixed points A and B is the perpendicular bisector of the straight line AB. y1 ) is The equation of the locus of a moving point P ( x. Equation of Locus ( use the formula of distance) The equation of the locus of a moving point P ( x.Formulae List SPM Form 4 Chemistry . y ) which is always at a constant distance (r) from a fixed point A ( x1 .com ONE-SCHOOL.Formulae List SPM Form 5 Physics . y1 ) and B ( x2 .one-school.List of Chemical Reactions All at One-School. y 2 ) with a ratio m : n is PA m = PB n The equation of the locus of a moving point P ( x.html 6 .NET Remember: y-intercept ⇒ x = 0 cut y-axis ⇒ x = 0 x-intercept ⇒ y = 0 cut x-axis ⇒ y = 0 **point lies on the line ⇒ satisfy the equation ⇒ substitute the value of x and of y of the point into the equation.net http://www. PA = PB ( x − x1 ) + ( y − y1 ) 2 = ( x − x2 ) 2 + ( y − y2 ) 2 2 PA = r ( x − x1 ) 2 + ( y − y1 ) 2 = r 2 ( x − x1 ) 2 + ( y − y1 ) 2 m 2 = ( x − x2 ) + ( y − y 2 ) 2 n 2 More Formulae and Equation List: SPM Form 4 Physics .
⎛1 ⎞ 2 N −F ⎟ m = L+ ⎜ ⎜ f ⎟C m ⎝ ⎠ m = median L = Lower boundary of median class N = Number of data F = Total frequency before median class fm = Total frequency in median class c = Size class = (Upper boundary – lower boundary) TN + TN m= 2 2 +1 TN + T N m= 2 2 +1 2 2 When N is an even number.net/notes.NET 07 Statistics Measure of Central Tendency Ungrouped Data Mean x= Σx N Without Class Interval x= Σ fx Σf Grouped Data With Class Interval x= x = mean f = frequency x = class mark Σ fx Σf x = mean Σx = sum of x x = value of the data N = total number of the data x = mean Σx = sum of x f = frequency x = value of the data = (lower limit+upper limit) 2 Median m = TN +1 2 m = TN +1 2 When N is an odd number. When N is an even number. When N is an odd number. Measure of Dispersion Ungrouped Data Grouped Data Without Class Interval With Class Interval variance x2 ∑ σ = 2 N −x 2 fx 2 ∑ σ = ∑f 2 −x 2 fx 2 ∑ σ = ∑f 2 −x 2 σ = variance Standard Deviation Σ(x − x ) σ= N 2 σ = variance σ= σ= Σ(x − x ) N Σx 2 − x2 N 2 σ = variance Σ f (x − x) σ= Σf 2 σ= Σx 2 − x2 N σ= Σ fx 2 − x2 Σf http://www.http://rahmahsamuri-rahms.com ONE-SCHOOL.blogspot.one-school.html 7 .
Interquartile Range Measures of Standard Deviation dispersion Variance No changes No changes No changes ×k ×k × k2 ÷k ÷k ÷ k2 08 Circular Measures Terminology Convert degree to radian: Convert radian to degree: × radians 180 D π degrees )radians 180 180 ) degrees x radians = ( x × xo = ( x × π π × π 180D Remember: 180D = π rad ??? 360 = 2π rad D 0.net/notes.7 rad O ??? 1.com ONE-SCHOOL.one-school.html 8 .2 rad http://www. mode Central Tendency Range .NET The variance is a measure of the mean for the square of the deviations from the mean. median.http://rahmahsamuri-rahms. The standard deviation refers to the square root for the variance.blogspot. Effects of data changes on Measures of Central Tendency and Measures of dispersion Data are changed uniformly with +k −k ×k ÷k +k −k ÷k ×k Measures of Mean.
net/notes.blogspot.http://rahmahsamuri-rahms.one-school.com ONE-SCHOOL.html 9 .NET Length and Area r = radius A = area s = arc length θ = angle l = length of chord Arc Length: Length of chord: Area of Sector: Area of Triangle: Area of Segment: s = rθ l = 2r sin θ 2 A= 1 2 rθ 2 A= 1 2 r sin θ 2 A= 1 2 r (θ − sin θ ) 2 09 Differentiation Gradient of a tangent of a line (curve or straight) dy δy = lim ( ) dx δ x →0 δ x Differentiation of a Function I y = xn dy = nx n−1 dx Example y = x3 Differentiation of Algebraic Function Differentiation of a Constant dy = 3x 2 dx y=a dy =0 dx a is a constant Differentiation of a Function II y = ax dy = ax1−1 = ax 0 = a dx Example y=2 dy =0 dx Example y = 3x dy =3 dx http://www.
net/notes. y = u5 . therefore du = 4x dx dy = 2(3) x 2 = 6 x 2 dx Differentiation of a Fractional Function 1 xn Rewrite y= y = x−n dy −n = − nx − n−1 = n+1 dx x therefore dy = 5u 4 du dy dy du = × dx du dx = 5u 4 × 4 x = 5(2 x 2 + 3) 4 × 4 x = 20 x(2 x 2 + 3) 4 Or differentiate directly y = (ax + b) n Example 1 y= x y = x −1 dy −1 = −1x −2 = 2 dx x dy = n.one-school.NET Differentiation of a Function III Chain Rule y = ax n dy = anx n−1 dx Example y = 2 x3 y = un u and v are functions in x dy dy du = × dx du dx Example y = (2 x 2 + 3)5 u = 2 x 2 + 3.http://rahmahsamuri-rahms.blogspot.html 10 .(ax + b) n −1 dx y = (2 x 2 + 3)5 dy = 5(2 x 2 + 3) 4 × 4 x = 20 x(2 x 2 + 3) 4 dx Law of Differentiation Sum and Difference Rule y =u±v u and v are functions in x dy du dv = ± dx dx dx Example y = 2 x3 + 5 x 2 dy = 2(3) x 2 + 5(2) x = 6 x 2 + 10 x dx http://www.a.com ONE-SCHOOL.
com ONE-SCHOOL.one-school.blogspot.NET Product Rule Quotient Rule y= u v v u and v are functions in x du dv −u dx dx v2 y = uv u and v are functions in x dy du dv = v +u dx dx dx Example y = (2 x + 3)(3 x 3 − 2 x 2 − x) u = 2x + 3 v = 3x3 − 2 x 2 − x du dv =2 = 9 x2 − 4 x − 1 dx dx dy du dv =v +u dx dx dx 3 2 =(3 x − 2 x − x)(2) + (2 x + 3)(9 x 2 − 4 x − 1) dy = dx Or differentiate directly y = (2 x + 3)(3x3 − 2 x 2 − x) dy = (3x3 − 2 x 2 − x)(2) + (2 x + 3)(9 x 2 − 4 x − 1) dx Example x2 y= 2x +1 u = x2 v = 2x +1 du dv = 2x =2 dx dx du dv −u v dy = dx 2 dx dx v dy (2 x + 1)(2 x) − x 2 (2) = dx (2 x + 1) 2 4 x2 + 2 x − 2 x2 2 x2 + 2 x = = (2 x + 1) 2 (2 x + 1) 2 Or differentiate directly x2 y= 2x +1 dy (2 x + 1)(2 x) − x 2 (2) = dx (2 x + 1) 2 4 x2 + 2 x − 2 x2 2 x2 + 2 x = = (2 x + 1) 2 (2 x + 1) 2 http://www.net/notes.http://rahmahsamuri-rahms.html 11 .
com ONE-SCHOOL.one-school. y1): mnormal = − 1 mtangent If A(x1. y1): dy = gradient of tangent dx Equation of tangent: y − y1 = m( x − x1 ) Gradient of normal at A(x1.http://rahmahsamuri-rahms. dy =0 dx d2y >0 dx 2 http://www. dx Equation of normal : y − y1 = m( x − x1 ) 1 − dy = gradient of normal Maximum and Minimum Point Turning point ⇒ At maximum point. Equation of tangent and Normal Gradient of tangent at A(x1.net/notes. dy =0 dx dy =0 dx d y <0 dx 2 2 At minimum point .html 12 .blogspot.NET Gradients of tangents. y1) is a point on a line y = f(x). the gradient of the line (for a straight line) or the gradient of the dy tangent of the line (for a curve) is the value of dx when x = x1.
blogspot.net/notes.com ONE-SCHOOL.NET Rates of Change Small Changes and Approximation Small Change: Chain rule dA dA dr = × dt dr dt δ y dy dy ≈ ⇒ δ y ≈ ×δ x δ x dx dx Approximation: ynew = yoriginal + δ y If x changes at the rate of 5 cms -1 ⇒ dx =5 dt Decreases/leaks/reduces ⇒ NEGATIVES values!!! = yoriginal + dy ×δ x dx δ x = small changes in x δ y = small changes in y If x becomes smaller ⇒ δ x = NEGATIVE http://www.http://rahmahsamuri-rahms.one-school.html 13 .
blogspot. when given 2 sides and 1 included angle 3 sides a A b b c 1 a b sin C 2 C is the included angle of sides a and b. when given 2 sides and 1 non included angle 2 angles and 1 side B A 180 – (A+B) a cos A = b2 + c2 − a 2 2bc A= a A b a Use.http://rahmahsamuri-rahms.one-school.net/notes. http://www.NET 10 Solution of Triangle Sine Rule: a b c = = sin A sin B sin C Cosine Rule: a2 = b2 + c2 – 2bc cosA b2 = a2 + c2 – 2ac cosB c2 = a2 + b2 – 2ab cosC Area of triangle: a C b Use.html 14 .com ONE-SCHOOL.
NET Case of AMBIGUITY A 180 . tan θ = c c b a (iii) Area = ½ (base)(height) http://www.com ONE-SCHOOL. cos θ = a . CB cuts the side opposite to C at 1 points Outcome: 2 solution Useful information: b a c Outcome: 1 solution θ In a right angled triangle. θ Remember : sinθ = sin (180° – θ) Case 2: When a = b sin A CB just touch the side opposite to C C B B′ Case 1: When a < b sin A CB is too short to reach the side opposite to C. (i) Phythagoras Theorem: c = a 2 + b2 (ii) Trigonometry ratio: sin θ = b . the point B can also be at point B′ where ∠ABC = acute and ∠A B′ C = obtuse. CB cuts the side opposite to C at 2 points Outcome: 1 solution Case 4: When a > b sin A and a > b. thus ∠AB′C = 180 – θ .http://rahmahsamuri-rahms. If ∠ABC = θ.blogspot. the length AC and length AB remain unchanged.net/notes. you may use the following to solve the problems.html 15 .one-school. Outcome: No solution Case 3: When a > b sin A but a < b.θ If ∠C.
com ONE-SCHOOL.C ×100 http://www.C = I A.http://rahmahsamuri-rahms.blogspot.net/notes. B × I B .one-school.NET 11 Index Number Price Index Composite index I = P 1 × 100 P0 I= Σ Wi I i Σ Wi I = Price index / Index number P0 = Price at the base time P1 = Price at a specific time I = Composite Index W = Weightage I = Price index I A.html 16 .